Survey of Physical Education Facilities and Infrastructure at Karang Endah 1 State Elementary School - Vina Oktaviana; Iyakrus; Soleh Solahuddin (Universitas Negeri Semarang, 2025)
This study aims to determine the infrastructure and facilities for physical education at State Elementary School 1 Karang Endah. The research used is in the form of quantitative descriptive research in the nature of a survey, in which research involves observing, recording the condition of objects or subjects in the field. The focus of this study is the population in this research is State Elementary School 1 Karang Endah, which will explain the state and quantity of infrastructure and facilities in the school to support the method of instruction and learning exercises. In order to gather data for this study, observation, documentation and literature. The instrument in this research is to use an observation sheet as a tool to collect data from the findings of the survey that was conducted. From the results of calculations of the availability and condition of infrastructure and facilities for physical education at State Elementary School 1 Karang Endah in athletics 6.25% games in the extremely bad category comprise 11.36% of the total, gymnastics 32.03% in the category lacking, martial arts sports 0% in the category of extremely poor. And the condition of physical education infrastructure in athletics is 16.6% Under the category of extremely poor, and games sports are 60% in the moderate category.